Including a general practice endorsement letter with the testing kit in the Bowel Cancer Screening Programme: Results of a cluster randomised trial. (December 2021) - Cross, Amanda J; Myles, Jonathan; Greliak, Paul; Hackshaw, Allan; Halloran, Stephen; Benton, Sally C; Addison, Caroline; Chapman, Caroline; Djedovic, Natasha; Smith, Stephen; Wagner, Christian von; Duffy, Stephen W; et al.
Objectives: To evaluate the effect of general practitioner endorsement accompanying the screening kit rather than with the invitation letter on participation in the NHS Bowel Cancer Screening Programme and on the socioeconomic gradient in participation in the Programme. Methods: The NHS Bowel Cancer Screening Programme in England is delivered via five regional hubs. In early 2016, we carried out a cluster-randomised trial, with hub-day of invitation as the randomisation unit. We randomised 150 hub-days of invitation to the intervention group, GP endorsement on the letter accompanying the guaiac faecal occult blood testing kit (75 hub-days, 197, 366 individuals) or control, usual letter (75 hub-days, 197, 476 individuals). The endpoint was participation, defined as return of a valid kit within 18 weeks of initial invitation. Because of the cluster randomisation, data were analysed by a hierarchical logistic regression, allowing a random effect for date of invitation. Socioeconomic status was represented by the index of multiple deprivation. Results: Participation was 59.4% in the intervention group and 58.7% in the control group, a significant difference ( p  = 0.04). There was no heterogeneity of the effect of intervention by index of multiple deprivation. We found that there was some confounding between date and screening episode order (first or subsequent screen). This in turn may have induced confounding with age and slightly diluted the result. Conclusions: General practitioner endorsement induces a modest increase in participation in bowel cancer screening, but does not affect the socioeconomic gradient. When considering cluster randomisation as a research method, careful scrutiny of potential confounding is indicated in advance if possible and in analysis otherwise.